Neighbors on Alert: a Difficult Role to Institutionalize. A Study in the City of Buenos Aires - Dikenstein, Violeta (FLACSO - Sede Ecuador, 2019)
Abstract In this article we propose to analyze the activity of a group of people, residents of a neighborhood in the south of the city of Buenos Aires, who make insecurity their area of intervention, exercise and "work", whom we call alert neighbors. From a qualitative perspective based on in-depth interviews with those involved in the process studied, and participatory observation in the scenarios where they circulate, we describe the profiles of the alert neighbors, the repertoire of activities that they carry out, the relationships they establish among themselves and with other actors, the bonds of coordination and conflict that they establish in this course, as well as the situations of interaction in which this role comes into play. We find that there is a shared repertoire of activities performed by these actors, varied within certain limits. Also, that the role of alert neighbor is subject to constant negotiation and redefinition, in the instances of meeting with various institutional authorities in charge of security.